First measurement of the charge asymmetry in beauty-quark pair production - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2014)
The difference in the angular distributions between beauty quarks and antiquarks, referred to as the charge asymmetry, is measured for the first time in b¯b pair production at a hadron collider. The data used correspond to an integrated luminosity of 1.0 fb−1 collected at 7 TeV center-of-mass energy in proton-proton collisions with the LHCb detector. The measurement is performed in three regions of the invariant mass of the b¯b system. The results obtained are Ab¯bC(40<Mb¯b<75 GeV/c2)=0.4±0.4±0.3%, Ab¯bC(75<Mb¯b<105 GeV/c2)=2.0±0.9±0.6%, Ab¯bC(Mb¯b>105 GeV/c2)=1.6±1.7±0.6%, where Ab¯bC is defined as the asymmetry in the difference in rapidity between jets formed from the beauty quark and antiquark, where in each case the first uncertainty is statistical and the second systematic. The beauty jets are required to satisfy 2<η<4, ET>20 GeV, and have an opening angle in the transverse plane Δϕ>2.6 rad. These measurements are consistent with the predictions of the standard model.